448 Multi-Cohort Study of the Mesenteric Fat from Crossbred Beef Steers Identifies Genes Associated with Body Weight Gain. (7th December 2018) - Lindholm-Perry, A; Freetly, H; Keel, B
Abstract: The purpose of this study was to identify differentially expressed genes (DEG) in the mesenteric fat associated with body weight gain that will be robust across a large segment of the cattle industry. Crossbred steers with high and low body weight gain and feed intake (2x2 factorial design) were selected from five different cohorts over three years. RNA sequencing was performed on mesenteric fat from the 80 selected steers (5 cohorts, each with 16 animals). A meta-analysis procedure was used to identify DEG across the five cohorts. Analyses for DEG were performed separately on each cohort using a generalized linear model with body weight gain and feed intake as main effects, and the resulting P-values were combined into a meta-P-value. A total of 41 DEG were associated with the main effect of gain in the meta-analysis (meta-PFDR< 0.05). These DEG were enriched for functions related to fatty acid metabolism due to the expression of ACLY, ACSM3, ACSL3. Genes that did not cluster into biological processes or pathways have functions in cell signaling, cell proliferation, oxidative stress, molecular chaperone, as well as immune and inflammatory responses were also identified. In this study, there were considerable differences between the DEG identified in each of the individual cohort analyses; however, the use of a meta-analysis allowed the identification of genes across these cohorts that were associated with weight gain in beef steers. These genes will be important for further evaluation to elucidate and validate their functional roles in body weight gain in cattle. USDA is an equal opportunity provider and employer.